Inhibition of ROS-mediated activation Src-MAPK/AKT signaling by orientin alleviates [H.sub.2][O.sub.2]-induced apoptosis in PC12 cells - Qi, Shimei; Feng, Zunyong; Li, Qiang; Qi, Zhilin; Zhang, Yao (Drug design, development and therapy, 2018)
Purpose: Reactive oxygen species (ROS) are considered a direct cause of neurodegenerative diseases (NDDs). Drugs developed to target ROS are effective for the treatment of NDDs. Orientin is a pyrone glucoside extracted from Polygonum orientale, and it exhibits many pharmacological activities. In this study, we aimed to determine whether orientin could relieve hydrogen peroxide ([H.sub.2][O.sub.2])-induced neuronal apoptosis and to investigate the specific target of orientin. Materials and methods: In this study, the neuroprotective effect and its possible mechanisms of orientin in mouse pheochromocytoma cell line (PC12) cells stimulated by [H.sub.2][O.sub.2], establishing an oxidative stress model, were investigated. And we further tested the role of ROS in the neuroprotective effects of orientin. Results: Orientin (5-100 [micro]g/mL) did not cause toxicity in PC12 cells but significantly decreased [H.sub.2][O.sub.2]-induced reduction in PC12 cell viability, cell apoptosis rates, and nuclear condensation. It also inhibited the activation of caspase-3 and degradation of poly(ADP-ribose) polymerase (PARP). Under the stimulation of [H.sub.2][O.sub.2], MAPKs (ERK, JNK, and p38), AKT, and Src signaling proteins in PC12 cells were activated in a time-dependent manner. The application of inhibitors that were specific for MAPKs, AKT, and Src effectively alleviated [H.sub.2][O.sub.2]-induced cell apoptosis. In addition, the Src inhibitor decreased the activation of MAPKs and AKT signaling. More importantly, orientin effectively decreased [H.sub.2][O.sub.2]-induced phosphorylation of MAPKs, AKT, and Src signaling proteins. Finally, we confirmed that orientin effectively inhibited [H.sub.2][O.sub.2]-induced accumulation of ROS in cells. In addition, ROS inhibitors blocked the Src-MAPKs/AKT signaling pathway-dependent cell apoptosis stimulated by [H.sub.2][O.sub.2]. Conclusion: These results indicate that alleviation of [H.sub.2][O.sub.2]-induced cell apoptosis by orientin is Src-MAPKs/AKT dependent. Overall, our study confirms that orientin alleviates [H.sub.2][O.sub.2]-induced cell apoptosis by inhibiting the ROS-mediated activation of Src-MAPKs/AKT signaling. Keywords: oxidative stress, orientin, neuroprotection, apoptosis, Src, MAPKs, AKT